AL-QUR’AN SEBAGAI MUNTAJ ṠAQĀFĪ: STUDI ATAS PEMIKIRAN NAṢR ḤĀMID ABŪ ZAID - Karom, Muhamad Noval (Ushuluna: Jurnal Ilmu Ushuluddin, 2021)
For Abū Zaid, the text is the result of reality, demanding a change in the reading of the text, in the end, there will be an integration between the text and reality. The meaning is static because it contains historical meaning, and the significance is dynamic. The concept he initiated began with the use of a contemporary study approach in understanding the process of al-Qur'an revelation. As a result, the sacredness of the text also the mean of Qur’an in Latin Kalāmullāh a deconstructed into a ‘culture product' meaning that text of the Qur’an is forming in its interactioning with socioculture. This research article will explain how the author supports the theory initiated by Naṣr Ḥāmid Abū Zaid in presenting the concept of Islam in formulating the idea of al-Qur'an as Muntāj Ṡaqāfī in today's contemporary era.